Perempuan dan Perilaku Kriminalitas: Studi Kritis Peran Stigma Sosial Pada Kasus Residivis Perempuan - Wanda Fitri (Kafa`ah: Journal of Gender Studies, 2017)
Criminality is one of the most andocentric acts (centered on men) based on public view. This perspective binds women to appropriate behaviors for women that are the atributes and behaviors that keep them from violating laws and crimes. Qualitative phenomenology was used in this research where the data taken from interview and observation which involved 5 women prisoners. Hence, when a woman is involved in a crime she will be considered very bad and labeled in ways that are negative and stereotypical. In the analysis of feminist criminology theories criticize that men are actually commit more crimes than women. Unfortunately, the women fall in a crime are caused by various factors. One among factor is the unfair treatment on women. Even in criminal acts women often get layered violence. They are not only judged as perpetrators but also become the victims. The punishment they received were not only in prison but also entail them after leaving the prison. The rejection and negative responses are also delivered from the environment reinforce the negative stigma about themselves. Stigma as criminals, unbelievers, and labeling as prisoners make it is difficult for them to adapt, find work, and become antisocial. The stigma develops along with the process of understanding (interpretation), the definition of criminals, and the differentiation of treatment that society gives to them (discrimination). The negative self-acceptance and self-acceptance became one of the triggers that pushed former female prisoners to repeat their criminal acts (recidivists).